BIOSIMILARS IN RHEUMATOLOGY - E. L. Nasonov (Научно-практическая ревматология, 2017)
One of the most striking achievements in the pharmacotherapy of rheumatoid arthritis (RA) and other human immunoinflammatory diseases (IIDs) late in the 20th century is associated with the design of a fundamentally new group of medications that received the name biological agents (BAs). However, the introduction of innovative BAs into clinical practice not only could enhance the efficiency of therapy and improve prognosis in patients with the most severe forms of IIDs, but has also led to a dramatic increase in the cost of treatment. Progress in the design of biosimilars is related to many factors, including expiry of the term of patents for many brand-name BAs, such as infliximab, adalimumab, etanercept, and rituximab. Over the last 5 years, a large number of biosimilars have been designed and their design is being continued. The European Medicines Agency, the World Health Organization, and the U.S. Food and Drug Administration have developed a regulatory framework and general requirements for the manufacture and characteristics of biosimilars. Federal Law No. 429-FZ «On Amendments to the Federal Law "On Circulation of Medicines"» dated December 22, 2014 defines a biosimilar drug as a biological medicine product that is similar to the parameters of quality, efficiency, and safety with the reference biologic drug in the same formulation, and the same route of administration. The review presents an update on the requirements for biosimilars used to treat IIDs, their interchangeability and promises in further clinical application. Particular emphasis is laid on the chimeric monoclonal antibodies to tumor necrosis factor-α infliximab biosimilar Flammegis (Egis Pharmaceuticals, Hungary), that has been registered in Russia for the treatment of RA, ankylosing spondylitis and other IIDs, as well as the chimeric monoclonal antibodies to B-lymphocytes rituximab biosimilar Acellbia in a phase III clinical trial that is in the closing stage. Preliminary provisions and recommendations of the All-Russian public organization «Association of Rheumatologists of Russia» concerning the place of biosimilars in rheumatology are formulated.